2018
DOI: 10.5334/gjgl.288
|View full text |Cite
|
Sign up to set email alerts
|

Selection, idioms, and the structure of nominal phrases with and without classifiers

Abstract: It is common to hypothesize that in classifier and non-classifier languages alike the various functional heads (determiner/demonstrative, numeral, classifier) each head their own projection, so that the maximal projection of the nominal phrase is not NP but something like DP. We evaluate the predictions this makes regarding selection and verb-object idioms in English, a nonclassifier language, and in Korean and Vietnamese, two classifier languages. These predictions are not upheld, and nominals act very differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 77 publications
0
37
0
1
Order By: Relevance
“…30 Second, there are cases where something similar happens with just the idiomatically interpreted nominal. This is arguably the case of the indefinite nominal in to have a ball, for which Bruening et al (2018) found no determiner variation. Here, a ball, which refers literally to a dance, according to the Oxford English Dictionary, is analogically connected to the associated effect or state that the dance produces, namely fun (cf.…”
Section: Factors Involved In Determiner Variabilitymentioning
confidence: 97%
See 4 more Smart Citations
“…30 Second, there are cases where something similar happens with just the idiomatically interpreted nominal. This is arguably the case of the indefinite nominal in to have a ball, for which Bruening et al (2018) found no determiner variation. Here, a ball, which refers literally to a dance, according to the Oxford English Dictionary, is analogically connected to the associated effect or state that the dance produces, namely fun (cf.…”
Section: Factors Involved In Determiner Variabilitymentioning
confidence: 97%
“…In a recent paper, Bruening et al (2018) discuss English (as well as Korean and Vietnamese) data from the internet, in which idioms do not occur with the canonical determiners they are commonly taken to occur with. Initial inspection shows considerable variety, and the change in determiner sometimes carries along with it a change in the number of the noun involved.…”
Section: Determiner Variability In Idiomsmentioning
confidence: 99%
See 3 more Smart Citations